The Use of Duolingo Application to Enhance English Vocabulary of Junior High School (RETAIN, 2020)
Teaching vocabulary is demanding in the context of English as a foreign language (EFL). EFL learners often forget words easily due to a lack of target language input, and most words are learned through classroom instruction, which often leads to boredom. Thus, such works suggest the urge for a more effective approach to vocabulary teaching for EFL learners. This study explores the use of MALL application; Duolingo to enhance student’s knowledge and interest in learning English vocabulary through mobile technologies. Quasi-experimental study was tested to seventh-grader with two group sample experimental and control that each group consist of 17 students. The research instruments used was a test that collected from pre-test and post-test score. Then, the data were analyzed using t-test calculation of SPSS 20 to identify its vocabulary improvement from each group. The results indicate a positive as the calculation of significance level (p-value) from experimental post-test scores is .000. It is lower than .05, which means there is a significant difference in experimental group after given a treatment. In addition, the experimental group got a higher average score of the post-test which is 87.94 than the control group which is 75.52. In conclusion, Duolingo can be believed to be a gamified language learning app that can develop vocabulary skills of the seventh grade.